Reisolamento, modificação estrutural e avaliação da atividade antimicrobiana de diterpenos de Viguiera arenaria - Rangel, Rander (2009)
With the re-insulation and purification work, two diterpenes were obtained in greater quantity, sufficient for the use of these products structural changes. With that, derivatives were obtained semi-synthetic 8 and 9 from acetylation of 4 and formation of sodium salt of 2. These nine diterpenes were submitted to the evaluation of their activity antimicrobial against a group of bacteria that includes important pathogens : Streptococcus piogenes ATCC 19615, Streptococcus pneumoniae ATCC 6305, Streptococcus sobrinus ATCC 33478, Streptococcus mitis ATCC 49456, Lactobacillus casei ATCC 11578, Streptococcus mutans ATCC 25275, Streptococcus salivarius ATCC 25975, Streptococcus sanguinis ATCC10556; and to a group of bacteria responsible for other human pathologies: Kocuria rhizophila ATCC 9341, Enterococcus hirae ATCC 10541, Staphylococcus aureus ATCC 9144, Staphylococcus aureus ATCC 6538, Staphylococcus aureus ATCC 29213, Bacillus subtilis ATCC 6051, Bacillus cereus ATCC 14579 The results obtained allow us to outline new objectives with regard to respect to obtaining derivatives and the subsequent comparison between the antimicrobial activity and the chemical structures identified, enriching the information obtained so far. This can make it possible to carry out structural modifications aimed at the development of new drugs at from the extracted prototypes.